Integrated multi-omics reveals novel microbe-host lipid metabolism and immune interactions in the donkey hindgut - Li, Yan; Ma, Qingshan; Shi, Xiaoyuan; Liu, Guiqin; Wang, Changfa (Frontiers in Immunology, 2022)
Evidence has shown that gut microbiota play a key role in host metabolism and health; however, little is known about the microbial community in the donkey hindgut as well as the interactions that occur between gut microbes and the host. This study aimed to explore the gut microbiome differences by analyzing the microbial community and differentially expressed genes (DEGs) related to lipid metabolism and the immune system along the donkey hindgut. The hindgut tissues (cecum, ventral colon, and dorsal colon) were separated, and the contents of each section were collected from six male donkeys for multi-omics analysis. There were significant differences in terms of dominant bacteria among the three sections, especially between the cecum and dorsal colon sites. For instance, species belonging to Prevotella and Treponema were most abundant in the cecum, while the Clostridiales_bacterium, Streptococcus_equinus, Ruminococcaceae_bacterium, etc., were more abundant in the dorsal colon. Apart from propionate, the concentrations of acetate, isobutyrate, valerate and isovalerate were all lower in the cecum than in the dorsal colon (p < 0.05). Furthermore, we identified some interesting DEGs related to lipid metabolism (e.g., ME1, MBOAT1, ACOX1, ACOX2 and LIPH) and the immune system (e.g., MUC3B, mucin-2-like, IL17RC, IL1R2, IL33, C1QA, and MMP9) between the cecum and dorsal colon and found that the PPAR pathway was mainly enriched in the cecum. Finally, we found a complex relationship between the gut microbiome and gene expression, especially with respect to the immune system, and combined with protein-protein interaction (PPI) data, suggesting that the PPAR pathway might be responsible, at least in part, for the role of the hindgut microbiota in the donkeys’ gut homeostasis. Our data provide an in-depth understanding of the interaction between the microbiota and function in the healthy equine hindgut and may also provide guidance for improving animal performance metrics (such as product quality) and equine welfare.